Development of an entrepreneurship system instrument to enhance the employability skills of Vocational High School (SMK) students - Baswedan, Aliyah Rasyid; Nurmahmudah, Fitri; Pujiati, Pujiati (Privietlab, 2025)
This study aimed to create an instrument for an entrepreneurship system that aids in improving the employability skills of Vocational High School (SMK) students. The background of the study stems from the persistent issue of unemployment that SMK graduates, in particular, face relative to graduates from other institutions, and the lack of a single instrument that can comprehensively assess the school entrepreneurship system’s performance. The adopted methodology is the research and development (R&D) technique, which aims to create an instrument, as outlined by Djemari Mardapi. The steps involved creating definitions, designing frameworks, drafting content, and undergoing validation to assess the expert viewpoint, followed by Aiken’s V index, the analysis of internal consistency using Cronbach’s alpha, and construct validity through Confirmatory Factor Analysis (CFA). The results indicate that the instrument developed has high content validity (Aiken’s V index from 0.85–1.00), excellent reliability (Cronbach’s alpha = 0.900), and adequate construct validity with a KMO of 0.948 and CFA model fit indices within the standard range. These indicators affirm that the instrument can be used to assess the entrepreneurship system in vocational schools.